Effects of biochars derived from chicken manure and rape straw on speciation and phytoavailability of Cd to maize in artificially contaminated loess soil. (15th December 2016) - Zhao, Baowei; Xu, Renzhi; Ma, Fengfeng; Li, Yewei; Wang, Lu
Abstract: While biochar can reduce the bioavailability of heavy metals in acidic soils and reduce their risk of entering the food chain, conditions for alkaline soils such as loess soils with high pH values, high carbonate content and low organic matter content remain unclear. Pot experiments were conducted to assess the effects of four rates (1%, 5%, 10%, and 15% w/w) of biochars prepared at 600 °C from chicken manure and rape straw (CBC and RBC) on soil properties, Cd speciation and phytoavailability, and plant growth in Cd contaminated (20 mg kg −1 ) light sierozem using maize ( Zea mays L.) as an indicator plant. Biochar additions significantly ( P  < 0.05) increased soil pH values, cation exchange capacity (CEC) and soil organic matter (OM). The results showed that Cd speciation turned somewhat into stable state as biochar application increased. When CBC and RBC was applied at the rate of 15%, the content of acid-extractable Cd decreased only by 16.3% and 11.64%, respectively. The uptake of Cd by maize shoots scarcely decreased with CBC and RBC amendment at the rate of 1% and 5%, respectively. Although it seemed that additions of more than 5% CBC or RBC significantly ( P  < 0.05) reduced Cd contents in maize shoots, maize growth was largely inhibited due to the high value of soil pH. These results could provide different implications for immobilization remediation of loess soils (e.g., light sierozem) contaminated with Cd. Highlights: Biochars significantly enhanced pH values of Cd contaminated light sierozem soil. Acid extractable Cd did not largely decrease with amendment of biochars. 1% and 5% of biochars did not lead to meaningful decreases in Cd uptake in maize. 10% and 15% of biochars significantly inhibited maize growth.